Synodality and the Subjectivity of the Laity in the Church - Bańka, Aleksander Ryszard (Ecumeny and law, 2024)
The XVI Ordinary General Assembly of the Synod of Bishops, initiated by Pope Francis on 9—10 October 2021 in Rome, under the watchword: "Towards a Synodal Church: Communion, Participation and Mission," involves lay people on an unprecedented scale in co-creating the synodal process. Why is this voice of lay people so important that it should be heard not only in the synodal process but — more broadly speaking — in the entire synodal style of functioning of the Church? This is connected with the fact that lay people are by no means an inferior part of the Church, what is more — the foundation of their subjectivity in the Church is not first of all the division into clergy and laity, which has a secondary meaning and specifies the nature of the vocation realized in the Church, but the Christian identity received with holy baptism. This article shows how Pope Francis, by developing the concept of synodality, consistently continues the council’s intuition of restoring lay people’s subjectivity in the Church and deepening the understanding of their Christian identity.